The Faculty of Medicine Struggle with the Credit Hour System - Adam, Hussein S. (مجلة الجزيرة للعلوم الصحية; مجلد 2 عدد 1 (2006), 2006)
The Beginning 1978: When I Joined the University of Gezira in 1977, the total number of academic staff was less than ten, including the Vice Chancellor and the Deans of Faculties. There were only four faculties: Agricultural Sciences, Economics & Rural Development, Science & Technology (changed later to Engineering & Technology) and Health Sciences (changed to Medical Sciences and later to Medicine under pressure from students of Batch I). The Credit Hour System was introduced to us in 1978 as a feasible system with many advantages. Given the required resources, it allows students to complete the needed courses and accumulate the required credit hours for graduation, each according to his abilities. Some students can graduate in less than five years while others may need six or seven years to graduate. The University of Gezira adapted